Supervisi Berbasis Coaching: Strategi Meningkatkan Kinerja Guru dalam Pembelajaran - Ummu Hani (Yayasan Sembilan Pemuda Indonesia, 2025)
Coaching-based supervision is an innovative approach to improving teacher performance through reflective dialogue and equal partnerships. This study aims to analyze the effectiveness of coaching-based supervision using a Systematic Literature Review (SLR) of 15 selected articles published between 2020 and 2025. The findings indicate that coaching enhances pedagogical competence (85%), work motivation (78%), and teachers’ reflective abilities (90%). Models such as TIRTA and peer coaching have proven effective, although challenges such as the limited time availability of school principals remain. These findings offer practical recommendations for the development of more transformative academic supervision.